Analysis of Purine Metabolism to Elucidate the Pathogenesis of Acute Kidney Injury in Renal Hypouricemia - Miyamoto, Daisuke; Sato, Nana; Nagata, Koji; Sakai, Yukinao; Sugihara, Hitoshi; Ohashi, Yuki; Stiburkova, Blanka; Sebesta, Ivan; Ichida, Kimiyoshi; Okamoto, Ken (Biomedicines, 2022)
Renal hypouricemia is a disease caused by the dysfunction of renal urate transporters. This disease is known to cause exercise-induced acute kidney injury, but its mechanism has not yet been established. To analyze the mechanism by which hypouricemia causes renal failure, we conducted a semi-ischemic forearm exercise stress test to mimic exercise conditions in five healthy subjects, six patients with renal hypouricemia, and one patient with xanthinuria and analyzed the changes in purine metabolites. The results showed that the subjects with renal hypouricemia had significantly lower blood hypoxanthine levels and increased urinary hypoxanthine excretion after exercise than healthy subjects. Oxidative stress markers did not differ between healthy subjects and hypouricemic subjects before and after exercise, and no effect of uric acid as a radical scavenger was observed. As hypoxanthine is a precursor for adenosine triphosphate (ATP) production via the salvage pathway, loss of hypoxanthine after exercise in patients with renal hypouricemia may cause ATP loss in the renal tubules and consequent tissue damage.
Keywords: acute kidney injury; xanthinuria; hypouricemia